KECURANGAN LAPORAN KEUANGAN DALAM PERSPEKTIF SYARIAH - Sarwo Edi; Asmaul Husna; Rahmi Amalia (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
Islam regulates all its affairs including human-human interaction, which is managed by Islam. The purpose of this study is to see how cheating behavior is seen in the Islamic context. The research method used in this study is a qualitative method with a literature review approach, where researchers collect information from international and national publications. The information collected from these journals was then used as research material for this study. Research findings indicate that the Qur'an and Hadith have provided clues or signs of fraudulent or fraudulent behavior. According to the results of the study, Islam has regulated all of its people, especially the problem of fraud, which is forbidden by Islam to be carried out by its adherents. Furthermore, this research shows that deception, which is often known as deception, has been practiced for centuries and Islam has clearly and passionately described how deception occurred and the consequences for its adherents. This study is also expected to help the public's understanding of fraud and activities, as well as enlightenment.